2007
DOI: 10.1021/cb700166z
|View full text |Cite
|
Sign up to set email alerts
|

Picomolar Inhibitors as Transition-State Probes of 5′-Methylthioadenosine Nucleosidases

Abstract: Transition states can be predicted from an enzyme's affinity to related transition-state analogues. 5'-Methylthioadenosine nucleosidases (MTANs) are involved in bacterial quorum sensing pathways and thus are targets for antibacterial drug design. The transition-state characteristics of six MTANs are compared by analyzing dissociation constants (K(d)) with a small array of representative transition-state analogues. These inhibitors mimic early or late dissociative transition states with K(d) values in the picom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(118 citation statements)
references
References 32 publications
2
116
0
Order By: Relevance
“…It was shown that the K d for p-ClPh-Thio-DADMe-ImmA was 570 pM for HpMTAN, an affinity roughly 100-fold higher than that of the ImmA analog that was demonstrated to have a K d of 40 nM (16). The differences in the affinities of the transition state analogs to structurally similar homologs of MTAN have been studied previously using computational techniques (38,39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the K d for p-ClPh-Thio-DADMe-ImmA was 570 pM for HpMTAN, an affinity roughly 100-fold higher than that of the ImmA analog that was demonstrated to have a K d of 40 nM (16). The differences in the affinities of the transition state analogs to structurally similar homologs of MTAN have been studied previously using computational techniques (38,39).…”
Section: Resultsmentioning
confidence: 99%
“…The DADMe-ImmA analogs represent a late dissociative transition state by containing a cationic nitrogen atom in the pyrrolidine moiety that represents a fully formed carbocation as well as having an elongated distance of 2.5 Å between the nonhydrolyzable adenine mimic and pyrrolidine moiety. Although previously published kinetic data identify HpMTAN as forming an early dissociative transition state during catalysis, the most potent transition-state analogs are DADMeImmA derivatives, which exhibit K d values in the picomolar range (16,17).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…Transition-state analogues that mimic the specific geometry and electrostatic features of a molecule can be used to predict the position of the transition state in the reaction coordinates (29). The dissociation constants of an array of transition-state analogue inhibitors were measured to explore the specificity of TgPNP.…”
Section: Resultsmentioning
confidence: 99%
“…Transition-state structures can be predicted based upon affinity to related transitionstate analogues. The transition-state characteristics are compared by analyzing dissociation constants (K i ) of an array of representative transition-state analogues (29). These inhibitors mimic known early or late dissociative transition states.…”
Section: Discussionmentioning
confidence: 99%